PENGARUH PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IV SD INPRES BONTOBILA - Risnawati; Sitti Fithriani Saleh; Ilhamuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low mathematical problem-solving abilities of elementary school students, caused by teacher-centered learning and a lack of active student involvement in the learning process. The purpose of this study was to determine the effect of implementing the Project-Based Learning (PjBL) model on the mathematical problem-solving abilities of fourth-grade students at SD Inpres Bontobila. This study used a quantitative approach with a pre-experimental approach and a One Group Pretest-Posttest Design. The subjects were 26 fourth-grade students of SD Inpres Bontobila in the 2025/2026 academic year. Data collection techniques included a mathematical problem-solving ability test, observation, and documentation. Data were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, the N-Gain test, and hypothesis testing (t-test) using SPSS version 26. The results showed an increase in students' mathematical problem-solving abilities after implementing the PjBL model. The average pretest score of 63.46 increased to 91.15 in the posttest. The results of the N-Gain test show an average value of 0.7378 which is in the high category, indicating that the PjBL model is effective in improving students' mathematical problem-solving abilities. In addition, the results of the hypothesis test show a Sig. (2-tailed) value of 0.000 <0.05, so that H₀ is rejected and H₁ is accepted. Thus, it can be concluded that the application of the Project Based Learning (PjBL) model has a significant effect on the mathematical problem-solving abilities of fourth-grade students of SD Inpres Bontobila